The Performance Evaluation of SAR for a Sausage Minkowski Square Patch Antenna - Ali, Israa H.; Ahmed, Riyadh Khlf (Al-Nahrain Journal for Engineering Sciences, 2018)
Square patch antennas (SPA) are widely used today's in wireless communication systems, mainly with popular frequency of 1.575 GHz. Wireless devices are the main source of propagation and radiation for the Electromagnetic (EM) rays. The waves penetrate tissues of the human beings and cause health danger. A fractal Sausage Minkowski square patch antenna is proposed, designed and simulated. A Fractal antenna is designed and simulated at 1.575 GHz for GPS application using CST MW studio 2014. Specific Absorption Rate (SAR) is the term which measures the exposure of human to electromagnetic waves radiation for communication antenna. SAR values are calculated over tissues mass with respect to the IEEE and (ICNIRP) standards for head safety. The SPA antenna presents the smallest SAR levels in adult head tissues at 2nd iteration Sausage Minkowski fractal antenna. The results show that the SAR levels for the three different fractal iteration are the highest in (ICNIRP) standard as compared to (IEEE) standard.